ECOLODGE DI KAWASAN TAHURA SULTAN ADAM - Feby Liliani Sari; Irwan Yudha Hadinata; Muhammad Tharziansyah (ULM Press, 2024)
Staycation has become a trend in various circles of society after the pandemic in meeting people's holiday needs. This trend is a potential for tourism development in the Tahura Sultan Adam, Banjar Regency which is useful for increasing regional economic income. However, at this design location there are regulations in construction in order to maintain environmental ecology. Therefore, it is necessary to design an ecolodge as a tourism accommodation that maintains environmental ecology using contextual methods. The application of this method is applied to the mass arrangement and visual form of the building. So as to produce an attractive tourism design that minimizes environmental damage.